A Comprehensive Experimental and Modeling Study on Dissolution in Li-Ion Batteries. Issue 8 (23rd April 2019) - Lee, Yoon Koo; Park, Jonghyun; Lu, Wei
Abstract : Dissolution is a critical challenge in metal oxide battery materials, which affects battery performance across multiple scales. At the particle level, the loss of active material as a result of dissolution directly results in capacity fade. At the electrode level, the re-deposition of dissolved metal ions onto the cathode increases cell polarization and hinders lithium transport. At the cell level, the dissolved ions further transport to and deposit on the anode, which consumes cycle-able lithium and leads to capacity fade. These processes lead to poor lithium reversibility, diffusivity, and conductivity. In this work, detailed experimental studies from the particle level up to the cell level are systematically conducted to provide parameters for model input and model validation. A multi-physics modeling framework is developed to reveal key mechanisms associated with metal-ion dissolution and their impact on battery performance. We simulate capacity degradation during cycling and compare the results to a series of experimental data such as cyclic voltammetry, electrochemical impedance spectroscopy, and battery cycling. The integrated study have revealed several key mechanisms related to dissolution, and quantitatively connected the particle level dissolution and deposition behaviors to the cell level performance. These can provide useful guidance for battery design and management.